The Pardubice Jews and their religious community to 1918 - Vojtková, Jitka; Kokeš, Luboš (Theatrum historiae, 2013)
This study describes the Jewish settlement of Pardubice from the first mentions of their residence in primary sources in the early 16th century to the period of the First World War. The main emphasis was put on the establishing and development of the Jewish religious community in the first half of the 19th century, its subsequent institutional consolidation and the resulting influence of the growing Jewish population on the economic, social and cultural emancipation of the town of Pardubice at the turn of the 19th and 20th century. There is also a list of the most important companies and businesses, including the introduction of the local Jewish significant personalities.